2009
DOI: 10.1111/j.1460-9568.2009.06773.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective innervation of lamina I projection neurons by cocaine‐ and amphetamine‐regulated transcript peptide (CART)‐immunoreactive fibres in the rat spinal dorsal horn

Abstract: Cocaine- and amphetamine-regulated transcript (CART) peptides have been implicated in spinal pain transmission. A dense plexus of CART-immunoreactive fibres has been described in the superficial laminae of the spinal cord, which are key areas in sensory information and pain processing. We demonstrated previously that the majority of these fibres originate from nociceptive primary afferents. Using tract tracing, multiple immunofluorescent labelling and electronmicroscopy we determined the proportion of peptider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The receptor of CART is yet unknown, but it has been suggested to potentiate spinal pain transmission [50] . A previous study in mice reported that ∼50% of the peptidergic nerve terminals in lamina I of the dorsal horn also contain CART [51] . We found high CART expression levels in a small subpopulation of sensory neurons by HCS microscopy (2.9±0.1%, n = 3, total of 11091 neurons, Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The receptor of CART is yet unknown, but it has been suggested to potentiate spinal pain transmission [50] . A previous study in mice reported that ∼50% of the peptidergic nerve terminals in lamina I of the dorsal horn also contain CART [51] . We found high CART expression levels in a small subpopulation of sensory neurons by HCS microscopy (2.9±0.1%, n = 3, total of 11091 neurons, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…CART has been shown to potentiate spinal N-methyl-D-aspartate (NMDA)-mediated nociceptive transmission [50] , [81] . Detailed studies on spinal cord sections of mice demonstrated that ∼50% of the peptidergic nerve terminals also contain CART [51] , [82] . Here we demonstrate that CART is expressed at high levels in a tiny subpopulation (≈ 3%) of sensory neurons co-expressing TRPV1.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis of the % of CGRP and NF200 nerve fibers co-expressing TrkA was adapted from previous methodologies (Herrero-Herranz et al, 2008, Kozsurek et al, 2009). Images were acquired with a 60× objective, under which it was possible to distinguish individual axons.…”
Section: Methodsmentioning
confidence: 99%
“…75 Cocaine-and amphetamine-regulated transcript peptide is a neuropeptide expressed in areas involved in pain processing, including peptidergic C fibers, primary afferents that terminate in the superficial laminae of the spinal cord. 42,43 Mechanistically, CARTp/GPR160-induced central sensitization is driven by activation of the mitogen-activated protein kinases (MAPKs) and extracellular signal-regulated kinase (ERK) and cAMP response element-binding protein (CREB). 75 It is well-documented that MAPK activation in the spinal cord is an integral component of neuroinflammatory process and a mechanistic hallmark of various persistent pain states.…”
Section: Introductionmentioning
confidence: 99%